Analisis Prioritas Penggunaan Dana Desa Berdasarkan Permendesa PDTT di Desa Tegalsambi Kabupaten Jepara Tahun 2016-2019 - Anggiase Alisiani Putri; Fatchur Rohman (Jurnal Rekognisi Akuntansi, 2020)
This study aims to determine the priority of using village funds in 2016 in Tegalsambi Village, Jepara Regency based on Permendesa PDTT number 21 of 2015, knowing the priority of using village funds in 2017 based on Permendesa PDTT number 22 of 2016, knowing the priority of using village funds in 2018 based on Permendesa PDTT number 19 of 2017, and knowing the priority of using village funds in 2019 based on Permendesa PDTT number 16 of 2018. The analytical method used is the method developed by Miller and Huberman which includes 3 activities carried out together, namely: (1) data reduction, (2) presentation of data, and (3) concluding. The results showed that the use of village funds in Tegalsambi Village, Jepara Regency in 2016 was by Permendesa PDTT number 21 of 2015 amounting to 99.07% prioritized in the field of village development and 0.93% in the field of community empowerment, the use of village funds in 2017 was by with Permendesa PDTT number 22 of 2016 amounting to 97.69% prioritized in the field of village development and 2.31% in the field of community empowerment, the use of village funds in 2018 has been by Permendesa PDTT number 19 of 2017 amounting to 80.89% prioritized in the field of development village and 19.11% for the field of community empowerment, and the use of village funds in 2019 was by Permendesa PDTT number 16 of 2018 which was 96.17% prioritized in the field of village development and 0.93% in the field of community empowerment.